The Implementation of Halal Tourism in Sharia Hotel Business - Kurniawan, Fendy; Safitri, Lia Ardiana (Media Wisata, 2023)
Halal tourism is part of tourism aimed at Muslim families who adhere to or obey Islamic law. The purpose of the study was to find out halal tourism applied at Syariah Hotel Solo in Surakarta. Knowing the obstacles applied in halal tourism at Syariah Hotel Solo in Surakarta. The results of the study Implementation and Syariah Hotel Solo in Surakarta is a process of integrating Islamic values into all aspects of activities at the hotel. The value of Islamic law as one of the elements of faith and belief adhered to by Muslims becomes a basic reference in building hotel activities. The criteria that must be met by every Islamic hotel in the form of Absolute Criteria that apply to the Hilal-1 Syariah hotel business. The obstacles applied in halal tourism at Sharia Hotel Solo in Surakarta are the absence of clear religious laws against Islamic hotels, many consider conventional hotels and Islamic hotels to be the same, the lack of promotion carried out by Islamic hotels, there is no support from Islamic mass organizations (Ormas), the lack of facilities that can attract public attention, there is an assumption that Islamic hotels are only specifically for Islam, it takes a relatively large amount of money to make facilities in Islamic hotels, for example: separate swimming pools, separate fitness or gym centers, construction of prayer rooms / mosques. Licensing at the National Sharia Council-MUI is still convoluted, which must meet the hilal-1 and hilal-2 criteria, as many as 26 items that must be met. There is still a complicated bureaucracy in licensing halal certification. The lack of sharia hotel certification is inversely proportional to the growing trend of increasing halal tourism. There is no specific regional regulation governing the development and management of halal tourism and Islamic hotels in the Surakarta area.